Relationship between vitamin D and human immunodeficiency virus (HIV) viral load among HIV-infected patients in Kazakhstan - Zhamilya Nugmanova; Nimish Patel; Gulzhakhan M Akhmetova; Gulnara S Kurmangalieva; Malika K Abdumananova; Aikan A Akanov; Natalia G Kovtunenko; Louise-Anne McNutt (Journal of Infection in Developing Countries)
Introduction: Human immunodeficiency virus (HIV) is associated with inflammation. An association between vitamin D deficiency and inflammation also exists. Our study attempts to examine whether there may be a relationship between vitamin D and HIV viral load (HIV RNA) by: 1) characterizing the distribution of 25-hydroxyvitamin D (25-OHD), and 2) determining if 25-OHD is independently associated with HIV RNA. Methodology: A cross-sectional study among HIV-infected adults was conducted. Demographics, clinical / social / HIV characteristics and data on antiretroviral therapy were collected by questionnaire, medical records and laboratory testing. All patients provided blood samples. Bivariate and multivariate analyses were conducted to quantify the relationship between vitamin D and HIV RNA. Results: Among the 564 patients, the median (interquartile range, IQR) 25-OHD value was 24.42 (16.22 – 34.10) ng/mL. The mean (standard deviation, SD) log-HIV RNA was 3.51 (1.11) copies/mL. There were 304 patients (53.9%) with an undetectable HIV RNA (< 500 copies/mL). In the bivariate analyses, no differences were observed between patients with and without an undetectable HIV RNA in mean (SD) 25-OHD, 25-OHD insufficiency (< 30 ng/mL), or 25-OHD deciles. In the log-binomial regression analyses, there was no association between 25-OHD and an undetectable HIV RNA (prevalence ratio: 1.00, 95% confidence interval: 0.99 – 1.01, p = 0.67). Conclusions: No relationship was observed between 25-OHD and HIV RNA among HIV-infected patients in Kazakhstan.